From Insurgency to Stability Volume I: Key Capabilities and Practices - Rabasa, Angel (RAND Corporation, 2011)
This book identifies the procedures and capabilities that the U.S. Department of Defense, other agencies of the U.S. government, U.S. allies and partners, and international organizations require in order to support the transition from counterinsurgency, when the military takes primary responsibility for security and economic operations, to stability and reconstruction, when police and civilian government agencies take the lead.